2022
DOI: 10.1186/s11658-022-00400-1
|View full text |Cite
|
Sign up to set email alerts
|

Acquired drug resistance interferes with the susceptibility of prostate cancer cells to metabolic stress

Abstract: Background Metformin is an inhibitor of oxidative phosphorylation that displays an array of anticancer activities. The interference of metformin with the activity of multi-drug resistance systems in cancer cells has been reported. However, the consequences of the acquired chemoresistance for the adaptative responses of cancer cells to metformin-induced stress and for their phenotypic evolution remain unaddressed. Methods Using a range of phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Thus, the cells in CL2 are undergoing a process of dedifferentiation from being epithelial cells and activating the mesenchymal gene networks. Existing studies have reported that adaptive resistance is positively correlated with the acquisition of mesenchymal traits in cancer 74,75 . CL2 was enriched with signatures associated with metastasis and drug resistance.…”
Section: Scellbow Enables Pseudo-grading Of Metastatic Prostate Cance...mentioning
confidence: 99%
“…Thus, the cells in CL2 are undergoing a process of dedifferentiation from being epithelial cells and activating the mesenchymal gene networks. Existing studies have reported that adaptive resistance is positively correlated with the acquisition of mesenchymal traits in cancer 74,75 . CL2 was enriched with signatures associated with metastasis and drug resistance.…”
Section: Scellbow Enables Pseudo-grading Of Metastatic Prostate Cance...mentioning
confidence: 99%